Emphasize The Social Nature of Learning (Texas Journal of Multidisciplinary Studies, 2022)
This article outlines and discusses the Social Nature of Learning as it applies to an overall approach to CLT within second language education and suggests that second language teachers can actively implement more student–student collaboration in their classes so that the students can further develop their second language skills and abilities.